Endovascular Intervention as Management for Acute Limb Ischemia, Including the Rutherford Class IIb Ischemia: Korean Experience - Moon, Sung Mo; Kim, In Wha; Jeon, Gyeong Sik; Choi, Sun Young; Kim, Man Deuk; Lee, Gun (Journal of the Korean Society of Radiology, 2016)
Purpose To comparatively assess the outcomes between endovascular intervention and surgery as initial management for acute limb ischemia (ALI). Materials and Methods From April 2004 to March 2015, the medical records of 51 patients with ALI who were treated with intervention or surgery were reviewed. Patient baseline characteristics and procedural data were collected. Clinical outcomes were compared between patients classified according to the Rutherford criteria. Results A total of 39 limbs of 35 patients underwent intervention, and 16 limbs of 16 patients underwent surgery. The technical success rate was 82.1% and 75.0% in the intervention and surgery groups, respectively. The intervention group showed no procedure related mortality or major complication during follow-up, but one case of compartment syndrome was reported in the surgery group. The mean follow-up period was 23.4 and 16.6 months in the intervention and surgery groups, respectively. The primary patency rate at 12 months was 89.4% and 100%, and the limb salvage rate at 12 months was 97.2% and 87.1% in the intervention and surgery groups, respectively. Among 7 patients with technical failure of intervention, immediate surgery was required in 6 cases, and 2 major and 1 minor amputations were required during follow-up. Conclusion Endovascular therapy is a safe and effective treatment option that reduces and delays amputation in patients with ALI.